Up the HRD ladder : a guide for professional growth - Chalofsky, Neal; Lincoln, Carnie Ives (Reading, Massachusetts : Addision-Wesley Publishing Company, 1983)
Three years ago when we first began talking about writing this book, we knew then (as we know now) that because of its content it would serve as one of the missing links among the books that have been written about human resource development. We were impatient throughout that period to get our thoughts down on paper in order to share this information with you, the reader. That impatience eased the difficulties that naturally arise when one author lives in Connecticut and the other in Maryland. As the manuscript evolved, our meetings took on a lively intensity that enabled us to meet our publisher's deadline almost perfectly.
Why professional growth? -- What is HRD? -- What does an HRD professional do? -- Assessment and development planning -- HRD professional development alternatives -- HRD career development -- HRD staff development -- Your future in HRD.
Includes bibliographical references and index.
Keywords: EMPLOYEES